2017
DOI: 10.1111/eff.12348
|View full text |Cite
|
Sign up to set email alerts
|

From salmon to shad: Shifting sources of marine‐derived nutrients in the Columbia River Basin

Abstract: Like Pacific salmon (Oncorhynchus spp.), nonnative American shad (Alosa sapidissima) have the potential to convey large quantities of nutrients between the Pacific Ocean and freshwater spawning areas in the Columbia River Basin (CRB). American shad are now the most numerous anadromous fish in the CRB, yet the magnitude of the resulting nutrient flux owing to the shift from salmon to shad is unknown. Nutrient flux models revealed that American shad conveyed over 15,000 kg of nitrogen (N) and 3,000 kg of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Further analyses could simulate the effect of differing run sizes of anadromous salmonids on nutrient loads given adult run sizes. Similar analyses were recently done for nonnative American Shad using historical and current run sizes of Pacific Salmon, American Shad run sizes, juvenile population estimates from dam indices, and a long-term nutrient monitoring site downstream of McNary Dam (Haskell, 2017). These analyses indicated that the nutrient balances are a product of existing nutrient loads, reservoir retention times, adult run sizes, and the spatial extent of spawning.…”
Section: Effects Of Reintroduction On Nutrient Balancessupporting
confidence: 55%
“…Further analyses could simulate the effect of differing run sizes of anadromous salmonids on nutrient loads given adult run sizes. Similar analyses were recently done for nonnative American Shad using historical and current run sizes of Pacific Salmon, American Shad run sizes, juvenile population estimates from dam indices, and a long-term nutrient monitoring site downstream of McNary Dam (Haskell, 2017). These analyses indicated that the nutrient balances are a product of existing nutrient loads, reservoir retention times, adult run sizes, and the spatial extent of spawning.…”
Section: Effects Of Reintroduction On Nutrient Balancessupporting
confidence: 55%
“…These numbers for allis shad were also lower than the nitrogen and phosphorus loadings reported for other diadromous species. By comparison, Haskell (2018) found that the closely related American shad (Alosa sapidissima) imported over 15 000 kg N and 3 000 kg P annually in the John Day Reservoir (JDR) in the lower Columbia River over the 1997-2015 time period. Considering that the JDR has a surface area of 222.6 km 2 , the total amount of nitrogen and phosphorus associated with American shad spawning runs would be 67.38 kg.N.km 2 .year -1 and 13.48 kgP.km 2 .year -1 .…”
Section: Strengths and Limits Of The Methodologymentioning
confidence: 99%
“…3.1. Quantifying nutrient imports Following the approaches of Haskell (2018) and Barber et al (2018), it was assumed that adults were not feeding after entering rivers in order to only account for marine-derived nutrient inputs. A fish that has successfully migrated to a river after growing and maturing at sea is likely to: (i) die before reaching the spawning grounds and reproducing, (ii) die after reproduction (i.e.…”
Section: Partial Validation Of Estimated Fish Abundancesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, nearly 140 million hatchery reared juvenile salmon were released into the CRB, but there are many more juvenile shad. In John Day Reservoir alone, as many as 112 million juvenile shad are produced annually, with many more originating in other Snake and Columbia River reservoirs and the Columbia River Estuary [ 15 ]. Juvenile shad consume up to 80% of the available zooplankton production in John Day Reservoir during the time that subyearlings are also migrating seaward [ 16 ].…”
Section: Introductionmentioning
confidence: 99%